THU0175 Effects of Baricitinib on Multibiomarker Disease Activity Scores and Their Components in a Phase 2B Study in Moderate-to-Severe Rheumatoid Arthritis Patients. (9th June 2015) - Taylor, P.; Genovese, M.C.; Keystone, E.; Weinblatt, M.; Rancourt, J.; Nantz, E.; Schlichting, D.; Zuckerman, S.; Macias, W.
Abstract : Background: Baricitinib, an oral inhibitor of JAK1 and JAK2 signaling, improved the signs and symptoms in patients with active rheumatoid arthritis (RA) who were methotrexate inadequate responders (MTX-IR) in a double-blind, placebo (PBO) controlled study 1 . Objectives: To investigate how a quantitative, multibiomarker disease activity score (MBDA) and its individual components are affected by treatment with baricitinib 4 mg (n=50) once daily compared to PBO (n=79) during a 12 week treatment period in moderate-to-severe RA patients. Methods: Serum samples collected at baseline and Weeks 4 and 12 from patients in the study 1 were shipped frozen to Crescendo Biosciences for analysis 2 . MBDA scores and changes in individual MBDA components were subjected to post-hoc statistical analyses. Results: At baseline, the proportion of patients with low, moderate, and high MBDA scores were similar in the 2 groups, as were median MBDA scores (PBO=44 vs. baricitinib 4 mg=47). Unlike PBO-treated patients, baricitinib 4 mg patients had decreased MBDA scores at 4 and 12 weeks compared to baseline (baricitinib 4 mg =35.5 and 37.0 (p<0.001) vs. PBO=46.0 and 45.0, respectively). At both 4 and 12 weeks of treatment and compared to PBO, baricitinib-treated patients had significant decreases in MBDA components including C-Reactive Protein (CRP), Matrix metalloproteinase (MMP)-3, serum amyloid A (SAA), soluble TNF receptor (TNF-RI), VCAM-1, and YKL-40 (human cartilage glycoprotein 39). Compared to PBO, there were no significant (p>0.05) changes for baricitinib-treated patients at either timepoint for epidermal growth factor (EGF), MMP-1, or vascular endothelial growth factor-A (VEGF-A). For baricitinib-treated patients versus PBO, at 4 but not 12 weeks, Interleukin-6 (IL-6) and resistin were significantly decreased and at 12 but not 4 weeks, leptin was significantly increased. Conclusions: Consistent with other indices of disease activity 1, the treatment of MTX-IR patients with baricitinib 4 mg once daily resulted in a reduction in the MBDA scores, apparent by 4 weeks. Decreases in MBDA scores and the components were present at both 4 and 12 weeks. Reduction in the levels of inflammatory markers beyond those associated with an acute phase response is apparent in these patients. References: Keystone E et al., Ann Rheum Dis 2015;74(2):333-340. Curtis JR et al., Art Care Res 2012:64(12):1794-1803. Disclosure of Interest: P. Taylor Consultant for: Pfizer, Eli Lilly & Company, M. Genovese Grant/research support from: Abbvie, Astellas, Eli Lilly & Company, Galapagos, Pfizer, Vertex, Consultant for: Abbvie, Astellas, Eli Lilly & Company, Galapagos, Pfizer, Vertex, E. Keystone Grant/research support from: Abbott Laboratories, Amgen Inc., AstraZeneca Pharmaceuticals LP, Bristol-Meyers Squibb, F. Hoffman-La Roche Inc., Janssen Inc., Eli Lilly & Company, Novartis Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, UCB, Consultant for: Abbott Laboratories, AstraZeneca Pharmaceuticals LP, Biotest, Bristol-Meyers Squibb, F. Hoffman-La Roche Inc., Genentech, Janssen Inc., Eli Lilly & Company, Merck, Pfizer Pharmaceuticals, UCB, Speakers bureau: Abbott Laboratories, Astrazeneca LP, Bristol-Meyers Squibb Canada, F. Hoffman-La Roche Inc., Janssen Inc., Pfizer Pharmaceuticals, UCB, Amgen, M. Weinblatt Grant/research support from: Bristol-Meyers Squibb, Crescendo Bioscience, UCB, Consultant for: Abbvie, Amgen, Astra Zeneca, Bristol-Meyers Squibb, Crescendo Bioscience, Eli Lilly & Company, Pfizer, Roche, UCB, J. Rancourt Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, E. Nantz Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, D. Schlichting Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, S. Zuckerman Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, W. Macias Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company